Transporte de juvenis de curimbatá Prochilodus lineatus em diferentes densidades - Nascimento Goncalves, Andre Fernando (2010)
Transportation of curimbata Prochilodus lineatus juveniles in different densities. Tins study evaluated the effects of curimbata Prochilodus lineatus transportation in three densities (100, 150 and 250 g L-1) on survival, metabolic, ionic and hematological (red series) variables Curimbata juveniles were transported in plastic bag during six hours, and sampled before packing, immediately after die arrival, 24 and 96 hours after transportation During recovery, higher mortality was seen in fish transported in die highest density Water variables, such as conductivity and total ammonia, presented increased values as density increased (p < 005). whereas the opposite occurred with dissolved oxygen Glucose level observed in the arrival was high, significantly reducing after 96 hours Among ionic variables, chloride decreased in higher fish densities and according to sampling times Red series hematological variables, such as hematocrit, red blood cell and hemoglobin, Increased in arrival, but diminished 96 hours after transportation There were no significant differences in the interaction between density and time of sampling for mentioned variables 250 g L-1 density induced the highest mortality rate and the worst variables values measured 96 hours of recovery after the stressing event was enough to return to initial values for hematological variables, but was not sufficient to return to initial values for metabolic and ionic variables.